Environmental analysis and its role in the success of the " organization " An analytical exploratory study in the Directorate of Water Resources / Babylon - Assi, Dr Nayef Ali; Jassem, Hameed (The journal of contemporary issues in business and government, 2021)
The research aims to know the role of environmental analysis by its dimensions (analysis of the internal environment, analysis of the external environment) in the success of the organization by its dimensions (efficiency of operations, attention to the customer, possession of resources, good management). The questionnaire was used as a method for collecting data, and a random sample of (50) individuals was chosen from the Water Resources Directorate / Babil. The research was based on two measures that were developed by the researcher based on the research literature and the nature and environment of the research and were subjected to validity and reliability tests. For the purpose of achieving the research objectives, the research was formulated. Two main hypotheses were tested by several statistical means using the ready-made statistical program (SPSS Var 22). The research concluded that there is an important impact of environmental analysis on the success of the organization.